The United States and Asia : regional dynamics and twenty-first-century relations - Sutter, Robert G. (Lanham: Rowman & Littlefield, 2015)
'Offers a cogent overview of the historical context and enduring patterns of U.S. relations with Asia ... Robert G. Sutter provides a balanced analysis of post-Cold War dynamics in Asia, which involve interrelated questions of security, economics, national identity, and regional institution building. He demonstrates how these critical concerns manifest a complex mix of realist, liberal, and constructivist tendencies that define the regional order. Sutter weighs how the recent US emphasis on're-engagement' with the broader Asia-Pacific fits within the context of regional dynamics. He assesses how the United States has responded to Asia's growing strength and importance while at the same time trying to maintain its leading position as an Asian power despite China's rising influence'--
Historical lessons and the evolution of US relations with Asia-Pacific -- Post Cold War developments -- The U.S. rebalance to the Asia Pacific -- Status and outlook of U.S. relations with China -- U.S. relations with Korea -- United States relations with Japan -- United States relations with Southeast Asia and the Pacific -- United States relations with South Asia -- U.S. relations with Central Asia, Mongolia and Russia in Asia -- Outlook and recommendations.
Includes bibliographical references and index.
Keywords: United States -- Foreign relations -- Asia; Asia -- Foreign relations -- United States; United States -- Foreign relations -- 21st century